How knowledge base factors change natural resource curse to economic growth?. (August 2018) - Sepehrdoust, Hamid; Zamani Shabkhaneh, Saber
Abstract: The aim of this study was to examine the possible role of knowledge based components, including social, financial and technological factors in motivating economic growth of developing oil based economies. For this purpose, a panel regression model is used to analyze the data collected from oil exporting developing countries (OPEC) during the years 2000–2016. The results extracted from an econometric model showed that an increment of one percent in social development, technological improvement and financial indexes has a significant positive impact on the gross domestic product (GDP) and caused economic growth to increase by 2.8, 0.67, and 2.2% respectively in selected OPEC countries. Moreover, the impact of the variables such as labor force, fixed capital formation, net inflow foreign direct investment and total reserves has a positive impact on the GDP growth, while, the impact of percentage of military expenditure to the GDP is negative on economic growth of selected countries. Highlights: While the challenge of Dutch disease prevailing in resource abundance OPEC countries caused the economies to change into resource curse status, that is believed that development of Knowledge Based factors, including, social improvement, broadening of financial markets and extensive use of technological equipments could pave the way for sustainable growth in these countries. The aim of this study was to examine the possible role of knowledge based components, including social, financial and technological factors in motivating economic growth of developing oil based economies. A panel regression model is used to analyze the data collected from oil exporting developing countries (OPEC) during the years 2000-2016. Results showed that an increment of one percent in social development, technological improvement and financial indexes has a significant positive impact on the gross domestic product (GDP) and caused economic growth to increase by 2.8, 0.67, and 2.2 percent respectively in selected OPEC countries. The impact of the variables such as labor force, fixed capital formation, net inflow foreign direct investment and total reserves has a positive impact on the GDP growth. The impact of military expenditure to the GDP is negative on economic growth of selected countries. In order to change the natural resource curse to natural resource endowment and economic growth, OPEC countries should have a formulated and prospective plan for the use of oil revenues and should attempt to use these incomes in generative and infrastructure investments in the society.